Alternative Resolution Patterns of Domestic Violence (KDRT) A Study of Baruga Village, Pa'jukukang District, Bantaeng Regency - Heri Tahir; Andika Wahyudi Gani; Berlian; Bahktiar (www.amertainstitute.com, 2026)
Domestic violence (Kekerasan Dalam Rumah Tangga/KDRT) remains a significant socio-legal issue in Indonesia, particularly in rural communities where cultural norms influence conflict resolution. This study aims to analyze the patterns of domestic violence and examine the effectiveness of alternative dispute resolution mechanisms in Baruga Village, Pa’jukukang District, Bantaeng Regency. A qualitative approach with a socio-legal perspective was employed to explore the interaction between formal legal frameworks and informal community practices. Data were collected through in-depth interviews, observation, and documentation, and analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings reveal that domestic violence in the study area predominantly affects women and manifests in three main forms: physical, psychological, and sexual violence. Physical violence is the most commonly reported, while psychological violence often precedes physical abuse, indicating a pattern of escalation. Sexual violence is underreported due to cultural stigma. The study also finds that most cases are resolved through informal mechanisms, particularly deliberation (musyawarah) and consensus (mufakat), facilitated by village authorities. Although these mechanisms are culturally accepted, they tend to prioritize reconciliation over justice and may not adequately protect victims. This study concludes that while alternative dispute resolution provides accessible and culturally relevant solutions, its effectiveness is limited by gender inequality, low legal awareness, and power imbalances. Strengthening legal literacy and integrating formal and informal mechanisms are essential to improve victim protection and ensure sustainable resolution outcomes.